Molecular diversity of Mycobacterium tuberculosis isolates in Treatment-experienced Patients from Andhra Pradesh, India - Srikar, Anagoni; Venkataramana, Banda; Mohan, Alladi; Sarma, PVGK; Rekha Devi, Kangjam; Narain, Kanwar; Chaudhury, Abhijit (The Journal of Infection in Developing Countries, 2023)
Introduction: To get a comprehensive idea about the transmission and epidemiology of TB globally and locally, the use of molecular typing methods has become imperative not only for understanding genetic diversity but also the population structure of Mycobacterium tuberculosis complex (MTBC). We aimed to investigate the drug resistance pattern and genetic diversity of MTBC among previously treated patients with sputum smear-positive pulmonary tuberculosis in a South Indian population. Methodology: 104 patients with sputum smear positivity and who had previously undergone treatment were selected. Drug susceptibility testing, Spoligotyping, MIRU-VNTR, and SNP typing were performed. Results: Mono-resistance to isoniazid 16 (15.38%) was the highest among all drugs. Out of 104 isolates, 24 (23%) isolates were classified as MDR strains. The distributions of most common lineages were: EAI3-Ind–20 (19.23%), EAI5-13 (12.50%), Beijing-12 (11.54%), CAS1-Delhi- 9 (8.65%), and 7 (6.73%) each of T-H37rv, Unknown and Orphan types. MIRU-VNTR-based analysis revealed that there are two major groups: CAS1-Delhi and Beijing groups. Out of 104 isolates, 82 belonged to well-defined lineages and 6 clusters, and the remaining 22 were singletons. SNP analysis showed no mutations associated with five sets of genes in 33 strains. Conclusions: The occurrence of 11.54% Beijing strains in South India is an important finding. High frequency of Isoniazid mono resistance noticed. Spoligotyping along with MIRU-VNTR and SNP typing is the best approach to the identification of strain lineages. No mutation with Antigen85C gene represents, can be used for vaccine candidates.